2021
DOI: 10.1155/2021/8833087
|View full text |Cite
|
Sign up to set email alerts
|

Noise Exposure Alters Glutamatergic and GABAergic Synaptic Connectivity in the Hippocampus and Its Relevance to Tinnitus

Abstract: Accumulating evidence implicates a role for brain structures outside the ascending auditory pathway in tinnitus, the phantom perception of sound. In addition to other factors such as age-dependent hearing loss, high-level sound exposure is a prominent cause of tinnitus. Here, we examined how noise exposure altered the distribution of excitatory and inhibitory synaptic inputs in the guinea pig hippocampus and determined whether these changes were associated with tinnitus. In experiment one, guinea pigs were ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 81 publications
2
6
0
2
Order By: Relevance
“…We identified that the hippocampal glutamatergic synapse pathway is associated with ARHL. This is consistent with previous reports wherein the glutamatergic synaptic connectivity in the hippocampus could be altered by noise exposure ( Zhang et al, 2021 ). Glutamate is the excitatory neurotransmitter at many synapses in the central nervous system and has been extensively studied in relation to cognition, particularly learning and memory.…”
Section: Discussionsupporting
confidence: 94%
“…We identified that the hippocampal glutamatergic synapse pathway is associated with ARHL. This is consistent with previous reports wherein the glutamatergic synaptic connectivity in the hippocampus could be altered by noise exposure ( Zhang et al, 2021 ). Glutamate is the excitatory neurotransmitter at many synapses in the central nervous system and has been extensively studied in relation to cognition, particularly learning and memory.…”
Section: Discussionsupporting
confidence: 94%
“…The hippocampus has been shown to expresses a higher level of Arc protein after acute noise trauma, which is critical to long-term potentiation and depression of synaptic transmission, and thus memory formation [ 43 ]. Specifically, reduced GABAergic synaptic densities and cholinergic inputs to the hippocampus were observed in noise-exposed animals that developed tinnitus-like behaviour compared to the controls [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Central maladaptive plastic changes in response to peripheral insult has become central dogma in the field of tinnitus ( Figure 7(6) ; Roberts et al, 2010 ; Langguth et al, 2013 ; Auerbach et al, 2014 ; Henton and Tzounopoulos, 2021 ). Data from animals and humans have found many unique but likely overlapping mechanisms to explain the neural plastic changes related to tinnitus which include: increases in spontaneous (non-sound evoked) firing rate neural activity ( Longenecker and Galazyuk, 2011 ; Berger et al, 2014 ; Galazyuk et al, 2019 ); increased incidence of neurons burst firing ( Ma et al, 2006 ; Bauer et al, 2008 ), increased or decreased neural synchrony ( Eggermont and Tass, 2015 ; Marks et al, 2018 ), thalamocortical dysrhythmia ( De Ridder et al, 2015 ), altered balance between excitatory and inhibitory neurotransmission ( Middleton et al, 2011 ; Llano et al, 2012 ; Ma et al, 2020 ; Zhang et al, 2021 ), cortical reorganization ( Engineer et al, 2011 ; Jeschke et al, 2021 ), and neural inflammation ( Fuentes-Santamaría et al, 2017 ; Wang et al, 2019 ; Deng et al, 2020 ). The mechanisms of hyperacusis are much less studied but are thought to have similar etiologies as tinnitus ( Auerbach et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%